Economic evaluation of projects in the electricity supply industry - Khatib, Hisham, 1936- (The Institution of Engineering and Technology, 2014)
In the highly capital-intensive electricity supply industry, it is essential that both engineers and managers understand the methodologies of project evaluation in order to comprehend and analyse investment proposals and decisions. This updated and expanded edition of Economic Evaluation of Projects in the Electricity Supply Industry takes a broad introductory approach, covering planning and investment, financial analysis and evaluation, risk management, electricity trading, and strategies, technologies, national requirements and global agreements for electricity generation in a carbon-constra.
Keywords: Electric utilities -- Finance -- Evaluation.; Electric utilities -- Economic aspects -- Evaluation.; elektronické knihy; electronic books